2021
DOI: 10.3390/children8030214
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perceptions and Experiences of Their Responsibilities for Their Alcohol Use—A Group Interview Study

Abstract: Young people often experiment with alcohol during adolescence, which is a period of their life that is characterized by increasing responsibility. Knowing how adolescents perceive responsibilities with regard to their alcohol use could prevent their alcohol consumption and help them to take responsibility for this aspect of their lives. This study describes adolescents’ perceptions and experiences of their responsibilities for alcohol use. We used a qualitative descriptive method that focused on 87 adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Using NVivo software helped us to achieve our research objectives, as this made the analysis process more systematic and helped us to increase the credibility. The uniformity of the secondary data, and their credibility with the qualitative original studies 28,32 confirmed their internal validity. The data collection and analysis process have been described in detail to enable transferability.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Using NVivo software helped us to achieve our research objectives, as this made the analysis process more systematic and helped us to increase the credibility. The uniformity of the secondary data, and their credibility with the qualitative original studies 28,32 confirmed their internal validity. The data collection and analysis process have been described in detail to enable transferability.…”
Section: Discussionmentioning
confidence: 69%
“…This was a deductive secondary analysis that explored the original datasets 28,32 of two studies conducted in Eastern Finland in 2017 (Figure 1). We used the consolidated criteria for qualitative research to ensure explicit and comprehensive reporting of the study and to improve its rigor, comprehensiveness, and credibility 33 .…”
Section: Design and Methodsmentioning
confidence: 99%